IgG4-Related Autoimmune Prostatitis: Is It an Unusual or Underdiagnosed Manifestation of IgG4-Related Disease? - María T. Bourlon; Mónica Sánchez-Ávila; Fredy Chablé-Montero; Ricardo Arceo-Olaiz (Case Reports in Urology)
IgG4-related disease (IgG4-RD) encompasses a wide range of extrapancreatic manifestations. Albeit some are relatively well known, others such as autoimmune prostatitis remain poorly described. We present a 61-year-old Latin-American male with autoimmune pancreatitis (AIP) who presented with lower urinary tract symptoms (LUTS), normal prostate specific antigen (PSA) test, and prostate enlargement attributed to benign prostatic hyperplasia (BPH). He underwent a transurethral resection of the prostate (TURP) after which symptoms were resolved. On histopathology, prostatic stroma had a dense inflammatory infiltrate rich in plasma cells and lymphocytes; immunohistochemical morphometric assessment showed >10 IgG4-positive plasma cells/high power field (HPF). The diagnosis of IgG4-related prostatitis was postoperatively. We compared the patient characteristics with those of previous reports on Asian patients. Shared findings included prostate enlargement, LUTS (symptoms that can be confused with BPH), and PSA within normal limits or mild elevations. IgG4-related prostatitis is rarely considered as a preprocedural diagnosis, even in patients with evidence of IgG4-RD. Involved prostate zones include mainly central and transitional zones and less frequently the peripheral. Currently, there is insufficient data about the natural history and outcome. Whether steroids, transurethral resection, or both are the treatment of choice needs to be elucidated.